KAJIAN KELAYAKAN EKONOMI PEMBANGUNAN JEMBATAN LAYANG SIMPANG SELAYANG KOTA MEDAN - Amrizal Amrizal; Jeffry Lisra (Jurnal Teknik Sipil Unaya, 2015)
The purpose of this study is to create an economically effective flyover construction in Medan so that this study can inspire the local official. Total cost of the construction is Rp. 720 billion which consist of  Rp 10.8 billion of flyover base structure construction cost, mobilization and road hardening cost, design and supervision cost; Rp 7.641 billion annual maintenance unit cost; Rp 22.923 billion/5 years periodically maintenance cost; and Rp 4,375,000/m2 estimated  land acquisition cost. The calculated benefit is travel cost cut-off which is the difference between the total travel cost with and without project. The travel cost consists of Vehicle Operational Cost and Time Value. Based on year 2014 analysis, the total amount of the cut-off saving of Simpang Selayang Flyover is Rp 30.06 billion. Economic feasibility analysis of horizon years for 30 years showed that the benefit obtained based on NPV, which is Rp 61,1 billion, is not adequate enough for 12,5 % annual interest rate, this can be seen by the 10.99% Internal Rate Return (IRR), so, the value of Simpang Selayang Flyover construction is not economically feasible yet.